2019
DOI: 10.5585/gep.v10i1.11000
|View full text |Cite
|
Sign up to set email alerts
|

Uma proposta de utilização de gestão de risco para o Planejamento Acadêmico de uma Universidade Pública

Abstract: Diversos problemas ocasionados por falta de análise dos riscos podem impactar diretamente a execução de projetos em organizações. As universidades por sua vez podem utilizar a gestão de riscos como um conjunto de atividades coordenadas para dirigir e controlar seus projetos, tentando minimizar os impactos provocados nos ambientes acadêmicos. O presente estudo objetiva, a partir de uma metodologia qualitativa e exploratória, desenvolver uma proposta de utilização de Gestão de Risco em uma universidade pública. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 1 publication
0
9
0
1
Order By: Relevance
“…According to Wang et al (2018), risk management in higher education is inevitable, as the threats related to disasters, finance, information technology, maintenance, and research can directly affect the reputation and sustainable development of higher education, which could cause a crisis of survival for the institutions. Moreover, federal universities relate with various social segments by providing the teaching, research, and extension services demanded by the community and the market (Ramos et al, 2018;Sousa et al, 2018).…”
Section: Risk Management In Brazilian Federal Universitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Wang et al (2018), risk management in higher education is inevitable, as the threats related to disasters, finance, information technology, maintenance, and research can directly affect the reputation and sustainable development of higher education, which could cause a crisis of survival for the institutions. Moreover, federal universities relate with various social segments by providing the teaching, research, and extension services demanded by the community and the market (Ramos et al, 2018;Sousa et al, 2018).…”
Section: Risk Management In Brazilian Federal Universitiesmentioning
confidence: 99%
“…When conducting a study on risk management in universities, Sedrez and Fernandes (2011) verified various relevant risks, such as dropouts, difficulties in maintaining an economic surplus, human error, and image risks. In turn, the study by Ramos et al (2018) identified some relevant risks that can impact public universities, such as a lack of security in the system, insufficient financial transfers, and strikes. To overcome such obstacles, generic lists of risks can be frequently used to help avoid potential risks being ignored or forgotten (Hill & Dinsdale, 2003).…”
Section: Respondents' Perception Regarding the Challenges Of Adopting Risk Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Risk management in the public sector has become part of work, compliance, auditing, and corporate governance routines in Brazil (Brito, Pimenta, Souza, & Cruz, 2017;Ramos, Lima, Andrade, & Vasconcelos, 2019;Oliveira, Santos, Medeiros, Gurgel, & Silva, 2020). In this scenario, in 2018, the Brazilian Federal Court of Accounts (TCU) carried out an operational audit called Exposição da Administração Pública Federal a Fraudes e Corrupção (Exposure of the Federal Public Administration to Fraud and Corruption), to examine the prevention and detection mechanisms related to fraud and corruption in federal higher education institutions (IFES).…”
Section: Introductionmentioning
confidence: 99%